A Halal Certification and Its Effect on Sales Growth; A Case of Halal Certified Food Producers in Banten Province - Isti Nuzulul Atiah; Najmudin Najmudin; Syihabudin Syihabudin (Al Qalam, 2022)
The Muslim community as consumers have the right to get correct information about the food products they consume. The government's efforts to protect the rights of the Muslim community in terms of information on halal food products, namely by issuing Law no. 33 of 2014 concerning Halal Product Guarantee. Halal certification is a form of producer strategy in attracting consumers to buy their products so that it will indirectly increase sales turnover. But the facts on the ground, there are still many SMEs, especially food producers who are still elements about the added value of halal certification. This study aims to analyze the effect of halal certification on increasing sales of food producers who already have halal certificates in the province of Banten. The research method used is quantitative. Methods of data collection using a questionnaire and data processing using SPSS software version 23. Data analysis using a simple linear regression method. The results of this study indicate that halal certification has a significant positive effect on increasing sales of halal-certified food producers in the province of Banten. The contribution of the effect of halal certification to the increase in sales is 21 percent, while the rest is influenced by other variables not examined in this study.